Designs of Learning and the Formation and Transformation of Knowledge in an Era of Globalization - Selander, Staffan (Studies in philosophy and education, 2008)
In this article, the formation and transformation of knowledge and the role of designs for learning will be elaborated and discussed in relation to the introduction of national curricula and school textbooks during the beginning of the industrialized era vs. the introduction of individual curricula and new digital learning resources in the post-industrialized era of globalization and multiculturalism. Quite different teaching and learning strategies have been emphasized, which I will call here “designed information and teaching” vs. “designs for learning”. It seems obvious that our current society is in a stage of change that requires a new understanding of knowledge, learning and identity formation. The new position and role of the learner underlines the productive and constructive aspect of learning. Pupils not only read texts, they also produce texts, pictures, film and music and they compile and edit virtual texts. Multimodal texts, as well as the information flow of the Internet, are the consequences of, and at the same time a vehicle for, new social patterns. “Learning Design Sequences” (LDS) is introduced as a theoretical map for the purpose of analyzing critical incidents in (a creative) learning process, using different genres, modes and media in a process of meaning-making.